(untitled) (Journal of Pharma Insights and Research, 2025)
A prospective observational study was carried out at Apollo Hospital, Kakinada, to evaluate the clinical outcomes of diabetic patients undergoing primary percutaneous coronary intervention (PCI) for acute myocardial infarction (MI). The study included 100 diabetic patients with acute MI over a 6-month period from October 2024 to February 2025. The study documented demographic characteristics, clinical presentations, electrocardiographic changes, and ejection fraction measurements at admission and discharge. Males constituted 61% of the study population, with the majority of patients (33%) falling in the 50-60 years age group. Anterior wall MI was predominant (58%) compared to inferior wall MI (42%). Acute onset chest pain was the primary presenting symptom in 33% of patients. At admission, 55% of patients showed ECG ST-segment elevation of 2-4 mm, while 45% showed elevation greater than 4 mm. Post-intervention assessment at discharge revealed significant improvement, with 47% of patients showing ST-segment elevation less than 2 mm. Similarly, left ventricular ejection fraction improved from baseline, with 49% of patients achieving 45-55% ejection fraction at discharge. The study showed that primary PCI effectively improved cardiac function in diabetic patients with acute MI, as evidenced by resolution of ST-segment elevation and enhancement in left ventricular function.